Method for selective photocatalytic degradation of pollutants by oxygen vacancy-containing Bi (at) Bi4Ti3O12 nanosheets
By using Bi@Bi4Ti3O12 nanosheets containing oxygen vacancies as photocatalysts, the cationic dyes in textile industry wastewater are selectively degraded under visible light irradiation, which solves the problem of difficulty in removing low concentration and high toxic pollutants in the prior art, and achieves an efficient and economical pollutant degradation effect.
Patent Information
- Application Number
- CN202311329623.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-13
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-10-13
AI Technical Summary
The prior art is difficult to effectively remove pollutants with low concentrations, high toxicity and difficult to degrade, especially cationic dyes in textile industry wastewater.
Bi@Bi4Ti3O12 nanosheets containing oxygen vacancies were used as photocatalysts to selectively degrade the cationic dye under visible light irradiation. This method uses ultrasonic dispersion of the catalyst to ensure that the pollutants and catalysts reach adsorption-desorption equilibrium, and then performs photocatalytic reactions under a xenon lamp to analyze the degradation efficiency of the pollutants.
It has achieved efficient degradation rate for cationic pollutants such as rhodamine B, methylene blue and alkaline orange II, reaching 95.47-99.31%, which is far higher than the degradation rate for anionic pollutants. It has simple operation and low cost, and is suitable for environmental protection fields such as sewage purification.
Smart Images

Figure BDA0004493809310000041 
Figure HDA0004493809330000011 
Figure HDA0004493809330000012
Abstract
Description
Technical Field
[0001] The present invention relates to a Bi@Bi4Ti3O 12 A method for selective visible light photocatalytic degradation of low-concentration, highly toxic and difficult-to-degrade pollutants using nanosheets. Background Art
[0002] Dye wastewater is an environmental pollutant that is toxic and carcinogenic to humans and other organisms, and usually comes from the textile and printing industries. The pollutants in dye wastewater are complex and can exist in the water environment for a long time, so it is necessary to develop suitable and reliable dye wastewater treatment methods. Current methods for treating dye wastewater usually include biodegradation, physical adsorption and chemical removal. However, the biodegradation method is inefficient, and the physical adsorption method only transfers the dye molecules from the wastewater to the surface of the adsorbent. The new pollutants generated still need subsequent treatment. In contrast, photocatalytic removal of dye molecules in dye wastewater has the advantages of thorough and reliable degradation and good economy.
[0003] Bi4Ti3O 12 As a bismuth-based Aurivillius-type composite oxide, the layered structure of alternating positive and negative charge layers gives it a strong interlayer electric field, which is conducive to carrier separation and migration from the bulk to the surface. The presence of oxygen vacancies can expand its light absorption range, promote electron transfer and provide reactive sites. The deposition of Bi as an electron acceptor further enhances its electron transfer and promotes carrier separation.
[0004] Photocatalytic selective degradation of cationic dyes in wastewater can remove specific dye molecules without affecting other dye molecules, which has certain practicality. 12 Bi@Bi4Ti3O2 has been reported as a photocatalyst for the removal of organic dyes, but has not been reported to contain oxygen vacancies. 12 Application of nanosheets for selective degradation of ionic dyes under visible light irradiation. Summary of the invention
[0005] The purpose of the present invention is to provide a Bi@Bi4Ti3O 12 A method for selectively degrading dyes by using nanosheets under photocatalysis. The method uses cationic dyes such as rhodamine B, methylene blue, and basic orange II as pollutants and degrades them in Bi@Bi4Ti3O 12In the presence of nanosheets, the catalyst is degraded under the irradiation of a xenon lamp. Studies have shown that the catalyst has selective degradation activity for the above pollutants, among which the degradation rate of cationic pollutants such as rhodamine B, methylene blue and basic orange II is as high as 95.47-99.31%, which is much higher than the degradation rate of most anionic pollutants (13.36%). The method of the present invention is simple to operate, low in cost, high in efficiency, and can selectively remove cationic dyes from textile industrial wastewater, and has good practical prospects in environmental protection such as sewage purification.
[0006] The present invention discloses a Bi@Bi4Ti3O containing oxygen vacancies 12 The method for selective photocatalytic degradation of low-concentration, highly toxic and difficult-to-degrade pollutants by nanosheets is characterized by the following steps:
[0007] a. Bi@Bi4Ti3O containing oxygen vacancies 12 Nanosheets were added to a concentration of 1×10 -5 mol / L cationic or / and anionic dye solution, ultrasonically dispersed for 5 min to make it uniform and stable, and then magnetically stirred for 30 min in a dark environment to ensure that the pollutants and catalysts reach adsorption-desorption equilibrium; every 20-30 (preferably 25) mg of Bi@Bi4Ti3O containing oxygen vacancies 12 The nanosheet corresponds to 100 mL of dye solution;
[0008] b. The reaction system was reacted under visible light irradiation, and 5 mL of the solution in step a was further transferred into a centrifuge tube, and then the beaker containing the remaining solution system was placed under a xenon lamp for illumination, and magnetic stirring was maintained at 350 r / min, and then 5 mL of the sample was sampled at fixed time intervals;
[0009] c. Centrifuge the sample and take the supernatant to test the UV-visible absorption spectrum to analyze the degradation efficiency of the pollutants.
[0010] The cationic dye in step a is rhodamine B, methylene blue, basic orange II or other dyes soluble in water in a cationic state; the anionic dye is methyl orange, acid red 18 or other dyes soluble in water in an anionic state; the cationic dye solution can be acidic, neutral or alkaline;
[0011] In step b, a 420nm filter is added to the xenon lamp to expand the light absorption range to the visible light region.
[0012] The fixed time period of the sampling interval in step b can be 2, 20 or 30 minutes.
[0013] The photocatalytic degradation of dyes by the catalyst of the present invention is generally applicable to cationic dyes because the catalyst surface is negatively charged and easily electrostatically attracts cationic dyes, but it is not unsuitable for all anionic dyes. For example, Congo red can be adsorbed on the catalyst surface by other means such as hydrogen bonds.
[0014] The selective photocatalytic degradation of cationic dyes by the catalyst of the present invention is shown in the condition that the solution pH is around 7 or the pH is greater than 7. The catalyst shows the selective photocatalytic degradation of cationic dyes. When the acid-base range is further widened to strong acidic or strong alkaline conditions, the catalyst still shows good visible light photocatalytic effect. The catalyst has obvious degradation activity for basic orange II, and still shows high-end catalytic activity under the acidic condition of pH 4, achieving 99.03% effective degradation within 60 minutes. The alkaline condition is further selected, and the degradation is carried out at a pH of 10, achieving 97.23% degradation within 120 minutes.
[0015] The present invention discloses a Bi@Bi4Ti3O containing oxygen vacancies 12 A method for selective photocatalytic degradation of cationic dyes by nanosheets. In this method, a certain concentration of representative cationic dye pollutants are irradiated under a xenon lamp, and all cations show a certain degradation effect. This is because when the pH of the solution system is 7, the catalyst surface carries a negative charge, which is beneficial to the adsorption of cationic dyes, thereby facilitating further photocatalytic degradation.
[0016] Taking cationic dyes such as rhodamine B, methylene blue, and basic orange II as pollutants, the Bi@Bi4Ti3O 12 In the presence of nanosheets, it is degraded under visible light irradiation. Studies have shown that the catalyst has selective degradation activity for the above pollutants, among which the degradation rate of cationic pollutants such as rhodamine B, methylene blue and basic orange II is as high as 95.47-99.31%, which is much higher than the degradation rate of most anionic pollutants (13.36%). The method of the present invention is simple to operate, low in cost, high in efficiency, and can selectively remove cationic dyes from textile industrial wastewater, and has good practical prospects in environmental protection such as sewage purification. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Bi@Bi4Ti3O containing oxygen vacancies in the present invention 12 The SEM image of the nanosheet shows that the catalyst is in the form of nanosheets, with a length and thickness of about 200 nm and 30 nm, respectively;
[0018] Figure 2 Bi@Bi4Ti3O containing oxygen vacancies in the present invention 12XRD diagram of nanosheets, curve a is the catalyst, short vertical line b is the standard PDF card, it can be seen from the figure that the catalyst is pure phase Bi4Ti3O 12 , there are no other impurities;
[0019] Figure 3 Bi@Bi4Ti3O containing oxygen vacancies in the present invention 12 XPS image of the nanosheet, from which we can see the existence of Bi element and oxygen vacancy OVs;
[0020] Figure 4 The degradation effect diagram of cationic dyes in Examples 1-3 and anionic dyes in Examples 4-5 is shown in the figure. It can be seen from the figure that Bi@Bi4Ti3O 12 The nanosheets have strong adsorption and photocatalytic degradation effects on the cationic dyes Basic Orange II, Methylene Blue, and Rhodamine B, and weaker adsorption and photocatalytic degradation effects on the anionic dyes Methyl Orange and Acid Red 18;
[0021] Figure 5 The degradation effect diagram of Example 6 shows that in the anionic and cationic dye mixed solution system, Bi@Bi4Ti3O 12 The nanosheets preferentially degrade cationic dyes;
[0022] Figure 6 In order to convert the Bi@Bi4Ti3O containing oxygen vacancies in Examples 1-5 12 Nanosheets replaced with control catalyst OVs-Bi4Ti3O 12 Degradation effect diagram.
[0023] Figure 7 Bi@Bi4Ti3O containing oxygen vacancies in Example 1 12 Photocatalytic degradation of cationic dye Basic Orange II by nanosheets over a wide pH range. DETAILED DESCRIPTION
[0024] The present invention is described in detail below with reference to the accompanying drawings and embodiments, but the present invention is not limited to the following embodiments.
[0025] The Bi@Bi4Ti3O containing oxygen vacancies of the present invention 12The nanosheet catalyst is mixed and ground for 30 minutes with 62.5 mmol of sodium chloride and potassium chloride as molten salt, then 5 mmol of Bi2O3 and 7.5 mmol of TiO2 are added and ground for 30 minutes to obtain a uniformly mixed powder; then urea (1.5 g) as a reducing agent is added to further increase oxygen vacancies, and grinding is continued for 30-60 minutes to obtain a uniform and fine powder; finally, the powder is moved into a crucible and placed in a muffle furnace, and the temperature is raised to 700°C at a rate of 2°C / min and calcined for 2 hours. After the reaction is completed, the temperature is lowered to room temperature at a rate of 2°C / min, and the sample is washed with a mixed solution of deionized water and anhydrous ethanol, dried at 60°C, and ground to obtain the target product.
[0026] In the synthesis of the catalyst, the reducing agent selected is urea, and other reducing agents may also be selected, such as glyoxal, ascorbic acid, sodium borohydride, glucose, lactic acid, tartaric acid, citric acid, etc., with urea being preferred; the amount of urea may be 0.0 to 3.5 g (preferably 1.5 g in the following embodiments).
[0027] Embodiment 1:
[0028] a. Dissolve 1.24 mg of cationic dye basic orange II in 100 mL of deionized water, and then treat it in ultrasound to make it a uniform and stable solution. Drain the uniform and stable solution into a 500 mL volumetric flask with a glass rod and make up the volume.
[0029] b. Take 100 mL of the solution obtained in step a into a beaker and transfer 5 mL into a centrifuge tube;
[0030] c. 25 mg of Bi@Bi4Ti3O 12 The nanosheets were added to the remaining solution in step b, and ultrasonically treated for 5 min to make it uniform and stable, and then magnetically stirred for 30 min in the dark to ensure complete adsorption of the dye molecules.
[0031] d. Pipette 5 mL of the solution in step c into a centrifuge tube, and then place the beaker containing the remaining solution system under a xenon lamp with a 420 nm filter, while maintaining magnetic stirring at 350 r / min. Take 5 mL of samples every 20 min, for a total of 7 times;
[0032] e. After centrifuging the sample, take the supernatant to test the UV-visible absorption spectrum and analyze the degradation efficiency of the pollutants.
[0033] Embodiment 2:
[0034] a. Dissolve 1.87 mg of cationic dye methylene blue in 100 mL of deionized water, and then treat it in ultrasound to make it a uniform and stable solution. Drain the uniform and stable solution into a 500 mL volumetric flask with a glass rod and make up the volume.
[0035] b. Take 100 mL of the solution obtained in step a into a beaker and transfer 5 mL into a centrifuge tube;
[0036] c. 25 mg of Bi@Bi4Ti3O 12 The nanosheets were added to the remaining solution in step b, and ultrasonically treated for 5 min to make it uniform and stable, and then magnetically stirred for 30 min in the dark to ensure complete adsorption of the dye molecules.
[0037] d. Pipette 5 mL of the solution in step c into a centrifuge tube, and then place the beaker containing the remaining solution system under a xenon lamp with a 420 nm filter, while maintaining magnetic stirring at 350 r / min. Take 5 mL of samples every 20 min, for a total of 7 times;
[0038] e. After centrifuging the sample, take the supernatant to test the UV-visible absorption spectrum and analyze the degradation efficiency of the pollutants.
[0039] Embodiment 3:
[0040] a. Dissolve 2.40 mg of the cationic dye Rhodamine B in 100 mL of deionized water, and then treat it in ultrasound to make it a uniform and stable solution. Drain the uniform and stable solution into a 500 mL volumetric flask with a glass rod and make up the volume.
[0041] b. Take 100 mL of the solution obtained in step a into a beaker and transfer 5 mL into a centrifuge tube;
[0042] c. 25 mg of Bi@Bi4Ti3O 12 The nanosheets were added to the remaining solution in step b, and ultrasonically treated for 5 min to make it uniform and stable, and then magnetically stirred for 30 min in the dark to ensure complete adsorption of the dye molecules.
[0043] d. Pipette 5 mL of the solution in step c into a centrifuge tube, and then place the beaker containing the remaining solution system under a xenon lamp with a 420 nm filter, while maintaining magnetic stirring at 350 r / min, sampling 5 mL every 2 min, for a total of 5 times;
[0044] e. After centrifuging the sample, take the supernatant to test the UV-visible absorption spectrum and analyze the degradation efficiency of the pollutants.
[0045] Embodiment 4:
[0046] a. Dissolve 1.64 mg of anionic dye methyl orange in 100 mL of deionized water, and then treat it in ultrasound to make it a uniform and stable solution. Drain the uniform and stable solution into a 500 mL volumetric flask with a glass rod and make up the volume.
[0047] b. Take 100 mL of the solution obtained in step a into a beaker and transfer 5 mL into a centrifuge tube;
[0048] c. 25 mg of Bi@Bi4Ti3O 12 The nanosheets were added to the remaining solution in step b, and ultrasonically treated for 5 min to make it uniform and stable, and then magnetically stirred for 30 min in the dark to ensure complete adsorption of the dye molecules.
[0049] d. Pipette 5 mL of the solution in step c into a centrifuge tube, and then place the beaker containing the remaining solution system under a xenon lamp with a 420 nm filter, while maintaining magnetic stirring at 350 r / min. Take 5 mL of samples every 20 min, for a total of 7 times;
[0050] e. After centrifuging the sample, take the supernatant to test the UV-visible absorption spectrum and analyze the degradation efficiency of the pollutants.
[0051] Embodiment 5:
[0052] a. Dissolve 3.02 mg of anionic dye Acid Red 18 in 100 mL of deionized water, and then treat it in ultrasound to make it a uniform and stable solution. Drain the uniform and stable solution into a 500 mL volumetric flask with a glass rod and make up to volume.
[0053] b. Take 100 mL of the solution obtained in step a into a beaker and transfer 5 mL into a centrifuge tube;
[0054] c. 25 mg of Bi@Bi4Ti3O 12 The nanosheets were added to the remaining solution in step b, and ultrasonically treated for 5 min to make it uniform and stable, and then magnetically stirred for 30 min in the dark to ensure complete adsorption of the dye molecules.
[0055] d. Pipette 5 mL of the solution in step c into a centrifuge tube, and then place the beaker containing the remaining solution system under a xenon lamp with a 420 nm filter, while maintaining magnetic stirring at 350 r / min. Take 5 mL of samples every 30 min, for a total of 5 times;
[0056] e. After centrifuging the sample, take the supernatant to test the UV-visible absorption spectrum and analyze the degradation efficiency of the pollutants.
[0057] Embodiment 6:
[0058] a. Set the concentration to 1×10 -5 50 mL of 2 mol / L anionic dye Acid Red 18 and 50 mL of cationic dye methylene blue were mixed in a beaker and treated with ultrasound.
[0059] b. Transfer 5 mL of the solution in step a into a centrifuge tube;
[0060] c. 25 mg of Bi@Bi4Ti3O 12 The nanosheets were added to the remaining solution in step b, and ultrasonically treated for 5 min to make it uniform and stable, and then magnetically stirred for 30 min in the dark to ensure complete adsorption of the dye molecules.
[0061] d. Pipette 5 mL of the solution in step c into a centrifuge tube, and then place the beaker containing the remaining solution system under a xenon lamp with a 420 nm filter, while maintaining magnetic stirring at 350 r / min. Take 5 mL of samples every 20 min, for a total of 7 times;
[0062] e. After centrifuging the sample, take the supernatant to test the UV-visible absorption spectrum and analyze the degradation efficiency of the pollutants.
[0063] Table 1
[0064]
[0065] Table 1 shows the Bi@Bi4Ti3O containing oxygen vacancies. 12 The final degradation rates of five dyes by nanosheets and control catalysts. Figure 4 , 5 It can be seen that the control catalyst Bi4Ti3O 12 There is no selective degradation effect on cationic dyes. Bi@Bi4Ti3O 12 The nanosheets are better than the control catalyst Bi4Ti3O 12 and OVs-Bi4Ti3O 12 It shows higher degradation rate and selectivity, which is attributed to the increase in oxygen vacancy concentration and the generation of Bi element.
[0066] Bi4Ti3O without oxygen vacancies and Bi 12 The catalyst has no selective degradation activity for the above pollutants, while the catalyst of the present invention exhibits high-end selective degradation activity relative to the control group. The catalyst of the present invention not only achieves efficient and selective degradation of pollutants in a neutral environment, but also exhibits high-end catalytic activity in a wide range of acidic and alkaline environments with a pH of 4-10.
[0067] The above embodiments and accompanying drawings illustrate the basic principles, main features and advantages of the present invention. The present invention is not limited to the above embodiments. The above embodiments and descriptions only illustrate the principles of the present invention. Within the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements are all protected by the present invention.
Claims
1. A Bi@Bi4Ti3O containing oxygen vacancies 12 Application of nanosheets for selective photocatalytic degradation of pollutants.
2. A Bi@Bi4Ti3O containing oxygen vacancies 12 The method for selective photocatalytic degradation of pollutants by nanosheets is characterized by: The following steps are involved: a. Bi@Bi4Ti3O containing oxygen vacancies 12 Nanosheets were added to a concentration of 1×10 -5 mol / L cationic or / and anionic dye solution, ultrasonically dispersed for 5 min to make it uniform and stable, and then magnetically stirred for 30 min in a dark environment to ensure that the pollutants and catalysts reach adsorption-desorption equilibrium; every 20-30 (preferably 25) mg of Bi@Bi4Ti3O containing oxygen vacancies 12 The nanosheet corresponds to 100 mL of dye solution; b. reacting the reaction system under visible light irradiation while maintaining stirring; c. Centrifuge the sample and take the supernatant to test the UV-visible absorption spectrum to analyze the degradation efficiency of the pollutants.
3. The method according to claim 2, characterized in that The cationic dye in step a is rhodamine B, methylene blue, basic orange II or other dyes soluble in water in a cationic state; The anionic dye in step a is methyl orange, acid red 18 or other dyes soluble in water in an anionic state.
4. The method according to claim 2, characterized in that The cationic dye solution may be acidic, neutral or alkaline.
5. The method according to claim 2, characterized in that In step b, a 420nm filter is added to the xenon lamp to expand the light absorption range to the visible light region.
6. The method according to claim 2, characterized in that The fixed time periods for the sampling intervals in step b include 2, 20 and 30 minutes.
7. The method according to claim 2, characterized in that Selective photocatalytic degradation of cationic dyes: When the solution pH is around 7 or greater than 7, the catalyst shows selective photocatalytic degradation of cationic dyes; when the acid-base range is further broadened to strong acidic or strong alkaline conditions, the catalyst still shows good visible light photocatalytic effect; it has obvious degradation activity for basic orange II, and still shows high-end catalytic activity under acidic conditions of pH 4, achieving 99.03% effective degradation within 60 minutes; further selecting alkaline conditions, degradation is carried out at pH 10, and 97.23% degradation is achieved within 120 minutes.
Citation Information
Patent Citations
Preparation method of black Bi4Ti3O12 photocatalyst
CN107008248A
Preparation method of activated bismuth titanate, and application of activated bismuth titanate as semiconductor photocatalyst
CN109513437A
Bismuth / bismuth titanate heterojunction hollow nanosphere and preparation method and application thereof
CN115318274A
Visible light-responsive photocatalyst and method for producing the same
WO2009116181A1
Sodium bismuth titanate catalyst
WO2023064984A1